Phage Therapy as a Rescue Treatment for Recurrent Pseudomonas aeruginosa Bentall Infection - Victor Eiferman; Pierre-Adrien Vion; Alexandre Bleibtreu (Viruses)
Phage therapy is experiencing renewed interest, particularly for antibiotic-resistant infections, and may also be useful for difficult-to-treat cases where surgery to remove foreign infected material is deemed too risky. We report a case of recurrent Pseudomonas aeruginosa endocarditis with Bentall infection treated successfully with a combination of antibiotics and phages.